2019
DOI: 10.3389/fcimb.2019.00357
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliferone Impedes Biofilm Formation and Virulence of Methicillin-Resistant Staphylococcus epidermidis via Impairment of Initial Attachment and Intercellular Adhesion

Abstract: Staphylococcus epidermidis is an opportunistic human pathogen, which is involved in numerous nosocomial and implant associated infections. Biofilm formation is one of the prime virulence factors of S. epidermidis that supports its colonization on biotic and abiotic surfaces. The global dissemination of three lineages of S. epidermidis superbugs highlights its clinical significance and the imperative need to combat its pathogenicity. Thus, in the current study, the antibiofilm activity of umbelliferone (UMB), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…For in vivo colonization assessment, worms were crushed in saline and plated on candida differential agar. Internal colonization was also observed under CLSM (Swetha et al, 2019;Valliammai et al, 2019). As this study is intended to evaluate the therapeutic potential of C. albicans for its application in oral candidiasis, safety evaluation was further evaluated with the HBEC.…”
Section: Gene Expression Profiling By Real-time Pcrmentioning
confidence: 99%
“…For in vivo colonization assessment, worms were crushed in saline and plated on candida differential agar. Internal colonization was also observed under CLSM (Swetha et al, 2019;Valliammai et al, 2019). As this study is intended to evaluate the therapeutic potential of C. albicans for its application in oral candidiasis, safety evaluation was further evaluated with the HBEC.…”
Section: Gene Expression Profiling By Real-time Pcrmentioning
confidence: 99%
“…Although knowledge of the antibiotic action of UMB is scarce, it has recently been demonstrated that derivates of UMB from plants of genus Ferula are useful against periodontal bacteria, inhibiting bacteria growth and biofilm formation [76]. In agreement with these data, it has been described that UMB can inhibit the formation of the biofilm created by Staphylococcus epidermidis, impairing intracellular adhesion by downregulation in the expressions of genes related to adherence function [77]. The MIC of UMB against different pathogens is shown in Table 4.…”
Section: Umbelliferon (Umb)mentioning
confidence: 81%
“…Coumarins downregulate the expression of curli and motility genes, which results in fewer fimbriae and the production of biofilm [ 84 ]. In the same sense, UMB prevents the formation of biofilm by the methicillin-resistant Staphylococcus epidermidis strain at a dose of 500 mg/mL but without affecting the growth of this bacteria [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…This action is carried out by reducing the expression of genes that code for factors involved in the formation of the bacterial biofilm, others that favor bacterial invasion such as agrA , those related to the production of hydrolases, and those of bacterial adhesion such as icaD, atlE, aap, bhp, ebh, sdrG, and sdr . Specifically, Umb is capable of reducing the expression of genes encoding exopolysaccharide (PIA) synthesis icaD , virulence and biofilm formation ( agrA ), intercellular adhesion and accumulation ( aap and bhp ), autolysin/adhesin ( atlE ), and ECM-binding protein ( ebh, sdrG, and sdrF ) [ 59 ]. It is noteworthy that coumarins have an antifungal activity against Candida albicans .…”
Section: Influence Of Itxasol© In the Expression Of Genes Related To Inflammation And Changes In Bacterial Genomicsmentioning
confidence: 99%